Collaborative Robots: Frontiers of Current Literature - Mikkel Stein Knudsen; Jari Kaivo-oja (Turkey, 2022)
Collaborative Robots (Cobots) play an increasing role in the advanced manufacturing landscape. The cobot market is rapidly expanding, and the academic literature is similarly growing. This paper presents a short overview of current cobotic trends and futures frontiers of the cobot development with particular emphasis on the role of cobots within the Industry 4.0-paradigm and within global megatrends. Since there is a strange, but distinct lack of literature reviews on the topic of collaborative robotics, the paper provides novel and valuable insights. In highlighting current frontiers, the paper also illustrates potential developments of future human-robot interaction.